The role of catechol-O-methyltransferase (COMT) in hippocampal function - Laatikainen, L (2010)
Catechol-O-methyltransferase (COMT) metabolises catechol-containing compounds, including dopamine. The aim of this thesis was to investigate whether COMT is involved in hippocampal function. This thesis also explored the role of functional polymorphisms within the COMT gene in the pathogenesis of schizophrenia and schizophrenia-related phenotypes. First, as part of a study investigating the role of COMT in schizophrenia, human hippocampal COMT mRNA levels were shown to be neither altered in schizophrenia or bipolar disease, nor affected by COMT genotype. Hence, functional COMT polymorphisms do not appear to operate by altering gross COMT mRNA expression. Importantly, this study showed that COMT is expressed in the human hippocampus. Second, the role of COMT in hippocampal neurochemistry was explored by studying the effect of pharmacological COMT inhibition on catecholamines and metabolites in rat hippocampal homogenates, and extracellularly, using microdialysis. Both demonstrated that COMT modulates hippocampal dopamine metabolism. Thus, hippocampal COMT is of functional significance with respect to dopamine. Third, the effect of COMT inhibition on hippocampus-dependent behaviour was investigated. The results suggested a memory-enhancing effect of pharmacological COMT inhibition on hippocampus-dependent associative and non-associative forms of short-term memory in rats. In contrast, acute COMT inhibition appeared to have no effect on behavioural correlates of ventral hippocampal function i.e. anxiety-like behaviour. In summary, the expression of COMT mRNA in the human hippocampus, as well as the effect of COMT inhibition on rat hippocampal neurochemistry and hippocampus-dependent behaviour provide evidence for a functional role of COMT in the hippocampus. Moreover, changes in COMT activity alter hippocampal dopamine metabolism, which could be a potential mechanism for the role of COMT in hippocampus-dependent short-term memory.